Navigating barriers to real-world evidence utilization for drug regulatory affairs and market access in Saudi Arabia - Sukkarieh, Hatouf H.; Al Fayez, Nourah; Al-Omar, Hussain Abdulrahman; Azmi, Nura O.; Syed, Bushra; Albar, Raed A.; Al Bali, Nawaf (Frontiers in Pharmacology, 2025)
BackgroundData-driven, evidence-based decision-making is crucial for guiding complex and often conflicting decision-making in health systems. This study explored the barriers and challenges faced by stakeholders in generating and using real-world evidence (RWE) in Saudi Arabia, focusing on pharmaceutical regulatory, reimbursements, and research landscapes.MethodsSemi-structured interviews were conducted with Saudi stakeholders working in regulatory organizations, research institutions, and the pharmaceutical industry using a topic guide. Purposeful sampling was used to select study participants. The interview topic guide included three main open-ended questions focused on the participants’ current experiences, existing barriers, and potential interventions for overcoming challenges. Thematic analysis was used to identify barrier- and challenge-related themes and subthemes.Findings11 stakeholders working in regulatory organizations, research institutions, and the pharmaceutical industry across Saudi Arabia were interviewed. Based on the interviews, we identified four major themes pertaining to the barriers and challenges related to advancing RWE use in Saudi Arabia: data management, local capabilities, resources, and governance. Each theme contained key subthemes.ConclusionThis study reveals critical barriers to RWE generation and utilization in Saudi Arabia. Having clear governance, policies, and guidelines for the collection, standardization, sharing, and utilization of real-world data is crucial for overcoming these barriers and challenges. A multifaceted policy approach characterized by stakeholder engagement, collaboration, and coordinated implementation efforts could help build a robust, unified RWE system that aligns with the Saudi Vision 2030 objectives for a sustainable, data-driven healthcare ecosystem.